(untitled) (Communications in Computational Chemistry, 2017)
Sulfonamide antibiotics are an important class of organic pollutant in the aquatic environments. To understand the hydrolysis behavior of sulfonamides, the hydrolysis mechanisms of a typical sulfonamide sulfachloropyridazine (SCP) were investigated using the density functional theory (DFT) at the B3LYP/6-31+G (d, p) level. SCP hydrolysis resembles nucleophilic substitution by water molecule attacking sulfonyl group (pathway 1) and heterocyclic aromatic ring (pathway 2) respectively. Due to the electrophilic center sulfur atom in pathway 1 carrying much larger positive charge than the carbon atom in the pathway 2, the sulfonyl group can be easily attacked by water molecule, and thus the pathway 1 can be dominant. By comparing the hydrolysis energy barrier of different forms of SCP, it was found that the SCP hydrolysis in neutral and once-protonated state are much more energetically favorable to proceed than the double protonated form. In addition, the hydrolysis path is not found for the dissociated anionic SCP. As the pH values in solution decreases, the corresponding neutral and once-protonated SCP increases, then the hydrolysis rate becomes faster, which is consistent with the experimental observations that the hydrolytic degradation rate at pH=4 is much faster than those of pH=7 and 9.